2016
DOI: 10.1002/2016gl070139
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical bounce resonance diffusion coefficient for waves generated near the equatorial plane

Abstract: Theoretical bounce resonance diffusion coefficient for waves generated near the equatorial plane with arbitrary wave normal angle distributions is derived. Previous studies either assumed waves to cover the whole bounce trajectory or to have only one wave normal angle for a given frequency. In this work, we theoretically derive a new bounce resonance diffusion coefficient without these limitations. We demonstrate that the pitch angle diffusion from bounce resonance is significant for near‐equatorially mirrorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 29 publications
3
76
0
Order By: Relevance
“…To investigate quantitatively the bounce resonant interactions between low‐frequency hiss and radiation belt electrons, we calculate the corresponding bounce resonance scattering rates following the method of Tao and Li (). The scattering rates are the summation over the bounce resonance order l from the lowest to the highest order and are proportional to the wave power spectral intensity.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate quantitatively the bounce resonant interactions between low‐frequency hiss and radiation belt electrons, we calculate the corresponding bounce resonance scattering rates following the method of Tao and Li (). The scattering rates are the summation over the bounce resonance order l from the lowest to the highest order and are proportional to the wave power spectral intensity.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…It has been proposed by Shprits () that magnetosonic and H + band electromagnetic ion cyclotron (EMIC) waves, which have frequencies comparable to the electron bounce frequency or its harmonics, have the potential to bounce resonate with near‐equatorially mirroring electrons by violating the second invariant associated with the electron bounce motion. Bounce resonant interactions with magnetosonic and H + band EMIC waves have been subsequently proved by recent studies (e.g., Chen et al, ; Cao et al, ; Li et al, ; Shprits, ; Tao & Li, ; Tao et al, ) to account for the pitch angle scattering of electrons with ~90° equatorial pitch angles. For typical plasmaspheric hiss with wave frequencies much higher than the electron bounce frequency, its bounce resonance with near‐equatorially mirroring electrons tends to be insignificant.…”
Section: Introductionmentioning
confidence: 95%
“…Based on previous theories (Cao et al, ; Tao & Li, ), the electron scattering rates caused by bounce resonance are given as follows: Dαα=DWWsin2αeqtanαeq2MBeq2,DαE=-DWWsin2αeqtanαeq2MBeq1γ,DEE=DWW1γ2, where DWW=12normalπpcosαeqmnormale2l=1scriptF(),lωbk[]W1l+W2l2+W3l2dk, W1l=lz0Jl()z0[]2θm+sin()2θm, W2l=||ll1ll=oddJl()z0[]sin()l+θ…”
Section: Effect Of Low‐harmonic Ms Waves On the Radiation Belt Electronsmentioning
confidence: 99%
“…Recently, wave‐particle interaction is put forward to explain the formation of butterfly distribution far away from the magnetopause. MS waves are believed to be a candidate mechanism responsible for the butterfly formation through Landau resonance (Horne et al, ; Li, Yu, et al, ; Xiao et al, ; Yang et al, ), transit time scattering (Bortnik & Thorne, ; Li et al, ; J. Li, Ni, et al, ; Ni et al, , ), and bounce resonance (Chen et al, ; Li & Tao, ; Maldonado et al, ; Shprits, ; Tao & Li, ). Landau resonance occurs when the parallel phase velocity ( ω / k ∥ ) of waves equals to the electron velocity parallel to background magnetic field ( v ∥ ; Artemyev et al, ) and the minimum resonant energy can be obtained according to the study of Horne et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MS waves have caught much attention because, by resonating with particles, they play a crucial role in radiation belt dynamics. On the one hand, numerous studies have found that these emissions are able to produce electron butterfly distributions via Landau resonance and bounce resonance energization (Horne et al, ; Shprits, ; Bortnik and Thorne, ; Li JX et al, ; Li LY et al, ; Ni BB et al, , ; Tao X and Li X, ; Xiao FL et al, ). On the other hand, MS waves are also found capable of interacting with protons through cyclotron resonance (Xiao FL et al, ; Fu S et al, ).…”
Section: Introductionmentioning
confidence: 99%